2017
DOI: 10.1111/ijfs.13625
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of different molecular weight fractions to anticancer effect of sweet potato protein hydrolysates by six proteases on HT‐29 colon cancer cells

Abstract: Summary The contribution of different molecular weight fractions to anticancer effect of sweet potato protein hydrolysates (SPPH) by six proteases on HT‐29 colon cancer cells was investigated. SPPH prepared by six proteases showed certain antiproliferation effect on HT‐29 cells. Compared with other five proteases, SPPH by Alcalase exhibited the highest antiproliferation effect with the lowest IC50 value of 119.72 μg mL−1. SPPH by Alcalase was further separated into four fractions (>10, 5–10, 3–5 and <3 kDa), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Journal Pre-proof among them, Alcalase hydrolysate was the one with the best results in terms of antiproliferative effects [772]. The peptides were tested in HT-colon cancer cells after being previously separated into four fractions.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Journal Pre-proof among them, Alcalase hydrolysate was the one with the best results in terms of antiproliferative effects [772]. The peptides were tested in HT-colon cancer cells after being previously separated into four fractions.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The peptides were tested in HT-colon cancer cells after being previously separated into four fractions. The highest anti-proliferative effect (43.87% at 100 μg/mL) was found in the fraction < 3 kDa [772]. Other less common protein sources have been used to this goal.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Compared with fresh sweet potatoes, the protein content in roasted sweet potatoes decreased, which may be associated with the involvement of proteins in the non‐enzymatic browning reaction during the thermal process (Wang et al, ). Previous study showed that the hydrolysates of sweet potato protein could inhibit the proliferation of colon cancer, and the hydrolysates in which molecular weight was lower than 3 kDa exhibited the highest anticancer activity (Zhang & Mu, ). As roots and tubers are often considered to be poor sources of protein, some sweet potato cultivars, such as Jizishu No.2, Longshu No.9, and Beijing No.553, which had high protein content, could be eaten fresh, and roasted for snack foods, desserts, and other staple foods from a nutritional and functional perspective.…”
Section: Resultsmentioning
confidence: 99%
“…SP is a common staple food in certain middle/low-income countries with great nutritional and functional potential. Its health benefits are not limited to its nutrients but also to other xenobiotics, including resistant starch [ 64 , 65 ], antioxidants [ 19 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 111 ], terpenoids [ 12 , 88 ], phytosterols [ 96 , 97 ], bioactive peptides [ 88 , 121 , 122 ] and many other phytochemicals that modulate key metabolic processes, reducing the odds for chronic illnesses including, yet not restricted to certain types of cancer [ 92 , 94 , 96 , 100 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ] and CVD. Further research should focus on understanding the physiological mechanisms and metabolic biotransformation of raw/processed SP’s bioactives whose intrinsic functionalities (e.g., anti-inflammatory, antioxidant, enzyme-inhibitory activity) target multiple target organs [ 88 , 89 , 90 ].…”
Section: Final Remarksmentioning
confidence: 99%
“…Personalized nutrition for cancer patients demands a continuous search for newer sources of phytochemicals to be used in complementary and alternative medicine. Several studies carried out in recent years [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ] have reported multiple control points determining the process of initiation, promotion, or the spread of cancer ( Table 4 ).…”
Section: Introductionmentioning
confidence: 99%